Verbal Sexual Harassment : Views of Indonesian Muslim Women - Amarnes, Vamia Tisensa; Fitri, Wanda; Wusqo, Urwatul; Elvina, Siska Novra (HUMANISMA : Journal of Gender Studies, 2023)
This study aims to determine women's views on verbal sexual harassment in terms of cognitive, affective, and conative factors. This is due to the increasing number of acts of sexual harassment that occur against women, one of which is in the public sphere. Forms of verbal sexual harassment that occurred in the form of whistling, negative speech, seduction, comments, sharp stares at body parts, or physical abuse The research method used is a qualitative method. Data were collected through observation and interviews. There were 33 participants involved in the research. The determination of research subjects used a purposive sampling technique. The research subjects were students of UIN Imam Bonjol Padang, UIN Sjech Djamil Djambel Bukittinggi, and UIN Mahmud Yunus Batusangkar. The research results show that on the cognitive aspect, there were participants who knew and did not know about verbal sexual harassment. In the affective aspect, all participants felt uncomfortable, irritated, anxious, and afraid. In the conative aspect, some informants resisted and some did not; this was because the participants were afraid of the perpetrators and did not want to ignore the actions they received. The implication of the research is to raise people’s awareness that harassment is not only physical but also verbal.